2019
DOI: 10.1111/febs.14980
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 activates MFN2 expression by binding to the promoter and decreases mitochondrial fission and mitophagy in HeLa cells

Abstract: Mitofusin‐2 (MFN2) is primarily involved in mitochondrial fusion and participates in diverse biological processes. Several reports show that MFN2 is a target of different miRNAs; however, the transcriptional regulation of MFN2 has not been extensively studied. To gain insight into the transcriptional regulation of MFN2, we expressed E2F transcription factor 1 (E2F1) exogenously and observed that it increased the endogenous expression of MFN2 by binding to its putative promoter region. Although the levels of E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
(73 reference statements)
2
10
0
Order By: Relevance
“…For instance, E2F1 induces CDCA5 transcription to accelerate hepatocellular carcinoma cell proliferation through AKT pathway (Chen, Chen, et al, 2019). E2F1 enhances MFN2 expression to hamper mitochondrial fission and mitophagy in HeLa cells (Bucha, Mukhopadhyay, & Bhattacharyya, 2019). Nonetheless, the function of E2F1 as a transcription factor in OSCC remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, E2F1 induces CDCA5 transcription to accelerate hepatocellular carcinoma cell proliferation through AKT pathway (Chen, Chen, et al, 2019). E2F1 enhances MFN2 expression to hamper mitochondrial fission and mitophagy in HeLa cells (Bucha, Mukhopadhyay, & Bhattacharyya, 2019). Nonetheless, the function of E2F1 as a transcription factor in OSCC remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, accumulative evidence has revealed that MFN2 was required for the induction of mitophagy by promoting depolarization-induced translocation of Parkin to the mitochondria [46,47]. However, some studies otherwise documented that MFN2 played a suppressive role in the activation of mitophagy by maintaining mitochondria-ER contacts and preventing the dissociation of mitochondria from the ER [25,26]. Our data showed that the down-regulation of MFN2 facilitated mitophagy via the induction of mitochondrial ssion under ER stress, supporting the suppressive effect of MFN2 on mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…S5a). MFN2 is a GTPase protein localized in the outer mitochondrial membrane as a crucial facilitator of mitochondrial fusion [25], and the reduction of MFN2 can be a trigger of mitophagy [26]. Therefore, we proposed that MFN2 down-regulation may be responsible for ER stress-induced mitochondrial ssion and mitophagy.…”
Section: Mitochondrial Ssion and Mitophagy Are Prominently Induced Unmentioning
confidence: 95%
“…Bucha et al . found that E2F1 modulated mitochondrial fusion and mitophagy, probably through regulation of MFN2. Bioinformatic analysis identified the E2F1–MFN2 axis as a regulator of mitochondrial morphology and mitophagy, which is the most direct evidence to show the relationship between E2F1 and mitophagy.…”
mentioning
confidence: 89%